THE INFLUENCE OF SENSITIVITY ON THE COGNITIVE DEVELOPMENT OF PRIMARY SCHOOL CHILDREN - Tursunov Lutfulla Saifullaevich (American Journals Publishing, 2024)
In this article, devoted to the influence of reason on the cognitive development of a child, as well as the role of knowledge in the acquisition of knowledge, special attention is paid to the mental ontogenesis of primary school children.
Keywords: Mind, non-intelligence, contemplation, perception, fantasy, memory, thinking, ontogenesis, activity, unconsciousness, awareness, knowledge, imitation, interest, ability.